The devil at Genesee Junction : the murders of Kathy Bernhard and George-Ann Formicola, 6/66 - Benson, Michael (Rowman and Littlefield, 2015)
The Devil at Genesee Junction recalls the mutilation murders of George-Ann Formiciola and Catherine Ann Bernhard that happened in June 1966 in the backfields of Chili, NY. The author, along with the help of a mother of one of the victims and a private detective, heats up the cold case, and sends the investigation in a startling new direction.